2020
DOI: 10.1016/j.jpaa.2019.106212
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of exact structures

Abstract: Examples of exact categories in representation theory are given by the category of ∆−filtered modules over quasi-hereditary algebras, but also by various categories related to matrix problems, such as poset representations or representations of bocses. Motivated by the matrix problem background, we study in this article the reduction of exact structures, and consider the poset (Ex(A), ⊂) of all exact structures on a fixed additive category A. This poset turns out to be a complete lattice, and under suitable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Lattice of exact structures revisited. We know by [BHLR,Theorem 5.3] that the class of exact structures on an additive category Ex(A) forms a lattice. In order to study the properties of this lattice, we show that it is isomorphic to the lattice of closed additive sub-bifunctors of Ext 1 A (−, −) defined in Section 4.…”
Section: Lattice Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Lattice of exact structures revisited. We know by [BHLR,Theorem 5.3] that the class of exact structures on an additive category Ex(A) forms a lattice. In order to study the properties of this lattice, we show that it is isomorphic to the lattice of closed additive sub-bifunctors of Ext 1 A (−, −) defined in Section 4.…”
Section: Lattice Structuresmentioning
confidence: 99%
“…Theorem 7.11. [BHLR,5.1,5.3,5.4] Let A be an additive category. The poset Ex(A) of exact structures E on A forms a bounded complete lattice (Ex(A), ⊆, ∧, ∨ E ) under the following operations:…”
Section: Lattice Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This lattice can be identified with the lattice of the subsets of the set of all the indecomposable objects that are not projective with respect to the maximal exact structure on A. Brüstle, Hassoun, Langford and Roy investigated relations between changes of exact structures to smaller ones (i.e. having strictly less conflations) and some matrix reduction problems, see [16] for the details (see also [26]). This inspired the name of the reduction of exact structures for this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In studying lengths of objects in exact categories, Brüstle, Hassoun, Langford and Roy [3,Exam. 6.9] showed that an analogue of the classic Jordan-Hölder property can fail for an arbitrary exact category; see also Enomoto [8].…”
Section: Introductionmentioning
confidence: 99%